Identification of key factors affecting the future of knowledge translation in Iranian health policy-making - Shahin Mojiri; Mohammad Reza Soleymani; Haniye Sadat Sajadi; Hasan Ashrafi-Rizi; Mandana Sahebzadeh; Mohsen Taheri Demneh (Journal of Education and Health Promotion, 2024)
BACKGROUND: Production, publication, and effective of academic research in health policy-making are tools to strengthen interactions between policy-makers, the scientific community, and the public. The purpose of this study was to identify the key factors of knowledge translation in the policy-making of the health system in Iran using the structural analysis method. MATERIALS AND METHODS: This future study was conducted using the foresight structural analysis method for a 10-year horizon in Iran from 2022 to 2031. Initially, 183 factors were identified by literature review and interviews with experts. In the next step, factors were reduced to 34 factors based on the research team’s opinions by merging similar items and removing fewer related items. Then, 34 factors were sent to the experts through an online questionnaire. Nineteen factors were identified with importance and uncertainty above the average. Then, the average degree of cross-impact of the selected factors in the matrix was scored by 11 experts in a focus group meeting, ranged from 3 (strong) to 1 (weak). The cross-impact of these factors was analyzed using MICMAC software. RESULTS: Five factors, including “policy-making method,” “role and function of universities,” “specialized services of knowledge brokering,” “international conflicts,” and “policy-makers’ trust in university researches,” were identified as key factors due to their high influence and effectiveness. CONCLUSION: The results of this study will help the research managers of the universities to be more informed and, therefore, more successful in their planning for more efficient utilization of the knowledge and evidence from academic research by knowing the factors influencing the translation of knowledge.